The effectiveness of supported employment for people with severe mental illness: a randomised controlled trial. - Burns, T; Catty, J; Becker, T; Drake, R; Fioritti, A; Knapp, M; Lauber, C; Rössler, W; Tomov, T; van Busschbach, J; White, S; Wiersma, D (2007)
BACKGROUND: The value of the individual placement and support (IPS) programme in helping people with severe mental illness gain open employment is unknown in Europe. Our aim was to assess the effectiveness of IPS, and to examine whether its effect is modified by local labour markets and welfare systems. METHODS: 312 patients with severe mental illness were randomly assigned in six European centres to receive IPS (n=156) or vocational services (n=156). Patients were followed up for 18 months. The primary outcome was the difference between the proportions of people entering competitive employment in the two groups. The heterogeneity of IPS effectiveness was explored with prospective meta-analyses to establish the effect of local welfare systems and labour markets. Analysis was by intention to treat. This study is registered with ClinicalTrials.gov, with the number NCT00461318. FINDINGS: IPS was more effective than vocational services for every vocational outcome, with 85 (55%) patients assigned to IPS working for at least 1 day compared with 43 (28%) patients assigned to vocational services (difference 26.9%, 95% CI 16.4-37.4). Patients assigned to vocational services were significantly more likely to drop out of the service and to be readmitted to hospital than were those assigned to IPS (drop-out 70 [45%] vs 20 [13%]; difference -32.1% [95% CI -41.5 to -22.7]; readmission 42 [31%] vs 28 [20%]; difference -11.2% [-21.5 to -0.90]). Local unemployment rates accounted for a substantial amount of the heterogeneity in IPS effectiveness. INTERPRETATION: Our demonstration of the effectiveness of IPS in widely differing labour market and welfare contexts confirms this service to be an effective approach for vocational rehabilitation in mental health that deserves investment and further investigation.